Leishmaniasis: A Menace - Alam, Mohammad Mumtaz (International Journal of Pharmaceutical & Biological Archive, 2017)
Leishmanisis is a disease caused by protozoan parasites of genus Leishmania which gets spread by thebite of female phlebotomine sandfly. This may be presented in patients in the form of either visceralleishmaniasis or post kala-azar or dermal leishmaniasis or cutaneous or mucocutaneous. More than 20species of Leishmania are responsible for causing infections in humans. Unfortunately, the affectedregions are often remote and unstable, with limited resources for targeting this deadly disease. The mosteffective diagnostic tests for leishmaniasis are invasive, potentially dangerous and samples are requiredfrom spleen, lymph nodes or bone marrow. Additionally, such diagnostic tests are not readily available inresource-poor and endemic areas. Different treatment options are available for treatment of this disease,with varying effectiveness and adverse effects. The paper herein highlights the problem of leishmaniasisalong with diagnostic options available, currently used drugs and different agents in the stage of preclinicaland clinical development.